Implementation of Event Risk Management in Minimizing Human Error at PT Indovision Prima Film - Lisa, Natasia Poetri; Widaharthana, I Putu Esa; Sumadi, I Gede (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
This study aims to explore the implementation of event risk management in minimizing human error during event documentation activities by PT Indovision Prima Film. The research methods used include in-depth interviews, documentation studies, and observations, followed by qualitative analysis of the collected data using risk dimension theory, ISO 31000:2018 risk management process, and human error classification. The results indicate that PT Indovision Prima Film has successfully implemented a risk management process to effectively minimize human error in event documentation, continuously adhering to the ISO 31000:2018 risk management process. The company is prepared to take further actions to strengthen its event risk management strategies, such as updating SOPs and implementing fair and educational sanctions to reduce the frequency and impact of human errors in event documentation activities, thereby minimizing potential losses.